Formation and development of digital skills in university education - Ihor Bondar (Laplage em Revista, 2021)
The aim is to develop a concept for implementing a systematic approach to the practice of forming and developing digital skills in higher education institutions. In this research, the methods of analysis and synthesis have been applied to integrate various approaches to the formation of digital skills into university education. Research results. Within the framework of a systematic approach to the formation and development of digital skills, consistent linking of the following approaches is suggested: standard-oriented, expert-oriented, student-oriented, problem-oriented. Integration of these approaches will ensure synergy in a changing technological environment. The main principles of a systematic approach are defined as processability, flexibility, and adaptability, problem orientation, timeliness, creativity. The scientific value of the research lies in the integration of various approaches that are practically used in university education to develop the concept of digital skills management.